Chemokine receptor CCR1 antagonist CCX354-C treatment for rheumatoid arthritis: CARAT-2, a randomised, placebo controlled clinical trial. Issue 3 (15th May 2012) - Tak, Paul P; Balanescu, Andra; Tseluyko, Vira; Bojin, Silvia; Drescher, Edit; Dairaghi, Dan; Miao, Shichang; Marchesin, Vittorio; Jaen, Juan; Schall, Thomas J; Bekker, Pirow
Abstract : Objectives: CCX354-C is a specific, orally administered antagonist of the C-C chemokine receptor 1, which regulates migration of monocytes and macrophages to synovial tissue. This clinical trial evaluated the safety and efficacy of CCX354-C in patients with rheumatoid arthritis (RA). Methods: CARAT-2 is a 12-week double-blind, randomised, placebo controlled trial in 160 patients with RA, with 68 tender joint count and 66 swollen joint count ≥8 and C-reactive protein (CRP) >5 mg/l, despite being on methotrexate for at least 16 weeks. Subjects received placebo, CCX354-C 100 mg twice daily, or 200 mg once daily for 12 weeks. Endpoints included safety (primary) and RA disease activity assessments based on American College of Rheumatology (ACR) response, and changes in 28-joint disease activity score–CRP, individual ACR components, as well as soluble bone turnover markers. Results: CCX354-C was generally well tolerated by study subjects. The ACR20 response at week 12 was 39% in the placebo group, 43% in the 100 mg twice daily group (difference and 95% CI compared with placebo, 4.5 (−14.1 to 23.1); p=0.62) and 52% in the 200 mg once daily group (13.0 (−5.8 to 31.8); p=0.17) in the intention-to-treat population, and 30% in the placebo group, 44% in the 100 mg twice daily group (14.4 (−5.9 to 34.8); p=0.17), and 56% in the 200 mg once daily group (25.8 (5.3 to 46.4); p=0.01) in the prespecified population of patients satisfying CRP and joint count eligibility criteria at the screening and day 1 (predose) visits. Conclusions: CCX354-C exhibited a good safety and tolerability profile and evidence of clinical activity in RA.